O atendimento às demandas da escola analisadas por ex-gestores/participantes da educação pública - Pereira, Robson da Silva (2008)
The school has been the subject of intense studies, research and various concerns. Besides, in Brazil, with the recent process of redemocratization, many professionals, especially teachers, holders of vocational curriculum with close liaison with school education at different levels, could ascend to? Public positions in the in City and Estate Departments of Education, Ministries and NGOs. This research aimed to find out which were their major contributions/ projects implemented and which ones were considered most important to improve school education and why. It was also of interest to know what they considere to be the major educational problems they faced and the reasons they were so considered. Six participants were interviewed according to a set of questions that aimed toprovide information on issues above mentioned, as well as other considered to be relevant. After transcription of the recorded tapes their speech were read in order to establish the issues considered most important to answer the questions of research. It was possible to show that their management experience in public education was marked by a strong commitment with the educational needs of schools, including teacher training and democratization of school management. On the other hand, the results exposed a significant gap between what is said to be best for schools and the effective conditions to make it real